Modelling and simulation of the mechanical behaviour of weft-knitted fabrics for technical applications: Part II: 3D model based on the elastica theory - Araújo, M. (2003)
This paper is in four parts. The first is related to general considerations and experimental analyses, and each of the others is related to different approaches to the theoretical analyses of the mechanical behaviour of weft-knitted fabrics and weft-knitted reinforced composites made of glass fibre. The objective is to find ways of improving the mechanical properties and simulating the mechanical behaviour of knitted fabrics and knitted reinforced composites so that the engineering design of such materials and structures may be improved. In Part II the first model is presented, a 3D model based on the classic elastica theory which is used to calculate the load-extension curves of a plain weft-knitted fabric in the coursewise and walewise directions. Good agreement is obtained between theoretical and experimental results.